2017
DOI: 10.1155/2017/7102514
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Compound Kushen Injection on Patients with Advanced Colon Cancer: A Meta‐Analysis of Randomized Controlled Trials

Abstract: Objective The efficacy and safety of Compound Kushen Injection (CKI) on advanced colon cancer remain controversial. We undertook a systematic meta-analysis of randomized controlled clinical studies on this issue. Methods A comprehensive literature search was conducted by searching the following electronic databases: PubMed, Cochrane, Chinese Biological Medical disc, Chinese National Knowledge Infrastructure, and Wan-Fang Database in China by the end of January 31, 2017, without language restriction. Meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…dIsCussIon CKI, as a TCM formula, has been approved by NMPA to treat cancer-induced pain. 17 The application of CKI for the treatment of a variety of cancer types has also been studied in breast cancer, 19 colon cancer, 20 nonsmall cell lung cancer, 21 acute leukemia, 22 and HCC. [23][24][25] Sorafenib, the first frontline drug, has been widely used for advanced HCC therapy for a long time.…”
Section: Cki Sensitizes Hcc To the Therapeutic Effects Of Subclinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…dIsCussIon CKI, as a TCM formula, has been approved by NMPA to treat cancer-induced pain. 17 The application of CKI for the treatment of a variety of cancer types has also been studied in breast cancer, 19 colon cancer, 20 nonsmall cell lung cancer, 21 acute leukemia, 22 and HCC. [23][24][25] Sorafenib, the first frontline drug, has been widely used for advanced HCC therapy for a long time.…”
Section: Cki Sensitizes Hcc To the Therapeutic Effects Of Subclinicalmentioning
confidence: 99%
“…[17][18][19] CKI has been applied to treat various solid tumor types clinically for the last 20 years, including liver cancer, lung cancer, breast cancer, gastric cancer, colorectal cancer, and other cancer types. [18][19][20][21][22] Notably, CKI was found to be effective in treating cancer-induced pain via the transient receptor potential cation channel subfamily V member 1 signaling. 17 Previous reports have shown that CKI used alone or combined with conventional chemotherapy enhances antitumor efficacy, reduces chemotherapy-induced toxicity, and improves quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…CKI is an ancient formulation in the Chinese pharmacopoeia; derived from a mixture of Radix sophorae flavescentis and Rhizoma smilactis glabrae herbs. Mixed results have been reported in breast cancer 51 . Here, we found CKI to down-regulate P53 pathway which is in line with a previous observation of P53 independent apoptotic cell death 17 , and up-regulate RTK-RAS-MAPK (EGFR, p38 and ErbB), PI3K-Akt-mTOR, NRF2 and TGF-beta pathways in MCF-7.…”
Section: Discussionmentioning
confidence: 92%
“…Compound Kushen Injection (CKI) is a traditional Chinese medicinal preparation that is widely used in clinics. Several recent meta-analyses were the most comprehensive analyses undertaken of currently available data regarding the treatment of patients with colon cancer and other advanced cancers with CKI combined with radiotherapy [6,14,15]. In these clinical reports, CKI enhanced the efficacy and reduced the toxic side effects of chemotherapeutic drugs since CKI improves immune function in patients with advanced cancer, thereby enhancing therapeutic efficacy [16].…”
Section: Discussionmentioning
confidence: 99%
“…CKI has been extensively used to treat cancer patients in a Chinese clinical setting in combination with chemotherapy for more than 15 years. Randomized controlled trials show significant efficacy of CKI in the treatment of advanced cancer especially colorectal cancer [6]. It has been demonstrated that CKI decreased the growth of colorectal cancer [7], hepatic carcinoma [8], human breast cancer [9], and gastric cancer cells [10]in vitro.…”
Section: Introductionmentioning
confidence: 99%